Exposure to high levels of perfluoroalkyl substances through drinking water and risk of cardiovascular morbidity and mortality in a Swedish register-based study - Zhou, Lucy; Andersson, Eva M; Harari, Florencia; Fletcher, Tony; Nielsen, Christel ; 0000-0003-3940-7847; Blomberg, Annelise J ; 0000-0003-1360-2580; Jakobsson, Kristina; Xu, Yiyi; Li, Ying (Environmental Research, 2025)
INTRODUCTION: Epidemiological studies focusing on the association of exposure to perfluoroalkyl substances (PFAS) with cardiovascular disease (CVD) morbidity and mortality are limited, with inconsistent findings. OBJECTIVES: This register-based study aimed to investigate the associations between exposure to PFAS and the risk of CVD morbidity and mortality in a Swedish population exposed to PFAS, dominated by perfluorohexane sulfonic acid (PFHxS) and perfluorooctane sulfonic acid (PFOS), through drinking water for decades. METHODS: The study included 46,553 individuals aged ≥30 who lived in Ronneby (1985-2013). Individual exposure status was evaluated based on yearly residential address and categorized into 'ever-high' and 'never-high'. Incident CVD morbidity (acute myocardial infarction [AMI], ischemic [IS] and hemorrhagic stroke [HS]), and CVD mortality were retrieved from national registries. Cox proportional hazards models estimated hazard ratios (HR). Further stratified analyses were performed by calendar year, sex and age (<50, 50-75, >75 years). RESULTS: Elevated risks were found for AMI (HR 1.10, 95 % confidence interval 1.01-1.19), IS (1.10, 1.00-1.22), HS (1.28, 1.03-1.59), and CVD mortality (1.15, 1.08-1.23) among individuals who had lived in the area with PFAS contaminated drinking water. Females showed higher risks for AMI and CVD mortality, while the risk of HS was higher among men. Stronger associations between PFAS and AMI and HS were observed in the age group 50-75 years. For PFAS-related CVD mortality, the point estimates increased with age though no significant interaction was observed. CONCLUSION: Our study suggests an association between high-level PFAS exposure and elevated risk of CVD morbidity and mortality.